Regular Film Property Changes of Konjac Glucomannan/Mung Bean Starch Blend Films. (6th April 2020) - Fang, Ying; Wang, Weiling; Qian, Hong; Wu, Kao; Xiao, Man; Ni, Xuewen; Jiang, Fatang; Chen, Sheng
Abstract: A series of konjac glucomannan (KGM) and mung bean starch (MBS) blend films with different mixing ratios are prepared, and their microstructure, molecular interactions, and film properties are evaluated. Results indicate that increased KGM content can contribute to the smoother and denser microstructure of the cross section of the KGM/MBS blend films, especially when it is >50%. Fourier transform infrared spectroscopy and X‐ray diffraction analysis indicate the existence of molecular interactions among the film components. A mixing ratio of KGM:MBS = 7:3 is suggested to have the optimum mechanical property, but other physical properties such as water contact angle, water vapor permeability (WVP), swelling and solubility, differential scanning calorimetry endothermic peak temperatures, and thermal gravimetric onset temperatures exhibit different change tendencies. These properties could be more impacted by the film's structure and intrinsic molecular properties than the molecular interactions. Moreover, high linearity against component ratio is observed for mechanical properties, water contact angle, swelling and solubility, and WVP, which may offer suggestions for film property predictions. The obtained results may offer suggestions to prepare edible films with desired properties based on KGM and MBS. Abstract : The film property changes of konjac glucomannan/mung bean starch blend films against mixing ratios are investigated. Some film properties show regular changes against the konjac glucomannan content with a high linear relationship or with a turning point, and some do not. The differences are caused by the impacts of film structure, intrinsic molecular properties, and molecular interactions.